Communicative strategies for the development of speaking skills in students of tenth grade at unidad educativa Almirante Alfredo Poveda Burbano”, Salinas, Santa Elena, academic year 2021-2022 - Solórzano Santistevan, Aslhey Danessa (2021)
English is by far the most widely spoken language on the planet, with millions of students acquiring it for a variety of reasons. As a result, pedagogists, English teachers, and others are looking for new resources and instructional approaches to help English language learners achieve high levels of proficiency. Despite the fact that there are numerous techniques for improving this skill, the proposed method is to employ drama as a teaching/learning strategy in English language courses. Since speaking ability is one of the pillars of English, independent of its extent, it is very essential in the growth of language learning acquisition. The purpose of this study is to enhance the speaking skills in students at level A1 by implementing dramatization. In order to develop this work, a qualitative-quantitative approach was used. Additionally, questionnaires, surveys, and xiii interviews were applied to the principal, teacher, and twenty-five pupils. The implementation of this research paper has the objective to assist teachers by providing several dialogues that can be used in class to practice speaking; furthermore, this study was designed to show that educators need to use their imagination to design dialogues that may instruct students in improving this necessary ability, which is speaking skill.